Factors influencing facebook usage at the workplace among the government servants of Putrajaya - Ahmad Amin, Ahmad Kamal Ariff; Adzharuddin, Nor Azura (Zes Rokman Resources, 2021)
The usage and utilization of particular social media such as social networking sites is growing rapidly in Malaysia and the recent trend shows that majority of Malaysians are using social media to communicate. Currently, Facebook is the most used social network among Malaysians with 22.7 million users in 2020, followed by Twitter, Pinterest and Instagram. The rising trend of Malaysian social media users is leading to an unavoidable increase in the number of office workers using social media at work. Employers are faced with a conundrum as they need to improve employee performance at work while controlling non-work-related Facebook usage during office hours. There are numerous studies on the effects of Facebook use in the workplace and its impact on job performance, but the results of Facebook use are mixed with positive and negative effects on the job performance. Therefore, this study aims to fill this gap by analyzing the social Facebook use at work among government servants in Putrajaya. This study examines how the use of social media such as Facebook at work affects the individual job performance of government servants in Putrajaya. The main purpose of the study was to examine the impact of Facebook use at work on job performance and to identify the factors that influence its use at workplace. The findings may be of great significance to government agencies and ministries reviewing their policies on employee use of social media in the workplace.